2016
DOI: 10.1002/leap.1006
|View full text |Cite
|
Sign up to set email alerts
|

Why do peer reviewers decline to review manuscripts? A study of reviewer invitation responses

Abstract: With peer review under closer scrutiny than ever before, research is needed toinvestigate not only what incentives encourage researchers to review manuscripts, but also what reasons prevent them from reviewing. We analysed responses to reviewer invitations sent by one journal in March to July 2015. The data showed that the overwhelming reason why reviewers decline is because they are unavailable to do so. Although the finding may not be surprising and confirms the findings of earlier research, the study illust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 1 publication
1
42
0
Order By: Relevance
“…The second reason was that the paper did not fall within their area of expertise. The proportion was higher than in another study (less than 5%) (Willis 2016). In order to improve the adequate selection of reviewers it is important that they provide accurate information about their areas of expertise, and also the editors need to respect reviewers' selfdeclaration of expertise.…”
Section: Reasons For Declining a Request To Review By Sexmentioning
confidence: 70%
See 1 more Smart Citation
“…The second reason was that the paper did not fall within their area of expertise. The proportion was higher than in another study (less than 5%) (Willis 2016). In order to improve the adequate selection of reviewers it is important that they provide accurate information about their areas of expertise, and also the editors need to respect reviewers' selfdeclaration of expertise.…”
Section: Reasons For Declining a Request To Review By Sexmentioning
confidence: 70%
“…Of those who declined to review the main reason was lack of time, similar to other studies (Tite and Schroter 2007) (Willis 2016). The second reason was that the paper did not fall within their area of expertise.…”
Section: Reasons For Declining a Request To Review By Sexmentioning
confidence: 85%
“…Despite this, there are few reviewers available to review and a general impression of low review rates [12], a pattern that is not explained by reviewer fatigue [10]. It is widely believed that a lack of incentives to review, coupled with the high workloads of academics is responsible for high rates of declines to review [11,22]. Whether they be financial in the form of direct payment or publication vouchers for open access journals [23], or with express allowance for reviewing in workload models [24][25][26], employers and publishers alike should facilitate reviews to rectify this.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited studies on why reviewers decline to review. Willis () studied reviewer invitation responses and he concluded that the main reason why reviewers decline is lack of time. This is the same reason that some of the JSE reviewers who declined explained by sending e‐mails to the editorial office.…”
Section: Discussionmentioning
confidence: 99%